Post a New Question

algebra

posted by .

Solve using the substitution method 6x-3y=18, 6x+3y=-12

  • algebra -

    Substitution:
    Rewrite each as:
    6x=3y+18
    6x=-12-3y
    Since they are both 6x, then
    3y+18=-12-3y
    =>
    6y=-30
    y=-5
    and
    x=(3*(-5)+18)/6=1/2


    By elimination (easier in this case)
    Add the two equations:
    6x-3y + 6x+3y = 18 -12
    12x=6
    x=1/2
    -3y=18-6*(1/2)
    y=-5

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

More Related Questions

Post a New Question